Social Solidarity in The Moment of The Prophet's Maulid: A Living Hadith Study on The Weh-Wehan Tradition during The Celebration of The Prophet's Maulid in Kaliwungu Community - Mohamad Nuryansah; Muhammad Izzul Haq (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
Kaliwungu is a sub-district in Kendal Regency, Central Java Province. This area has various local wisdom and traditions that have been carried out for generations, including the